Quantifying brown carbon light absorption in real-world biofuel combustion emissions. Issue 6 (21st April 2022) - Islam, Mohammad Maksimul; Neyestani, Soroush E.; Saleh, Rawad; Grieshop, Andrew P.
Abstract: Biofuel combustion is an important source of particulate light absorbing organic carbon (OC), also known as brown carbon (BrC). We applied spectrophotometry to characterize methanol-extracted BrC from emission tests of 'real-world' biofuel combustion in India and Malawi, including wood stoves ('traditional', 'improved' and 'chimney') and artisanal charcoal kilns. Average mass absorption coefficient (MACbulk, λ ) of extracted BrC was highest for 'traditional', followed by 'improved', 'chimney', and 'charcoal', at near-ultraviolet to blue wavelengths, with this order reversed for BrC absorption Angstrom exponent (AAE). MACbulk, λ in UV wavelengths was positively correlated with the elemental carbon to organic aerosol ratio (EC/OA), though the correlation was weaker than that observed in laboratory cookstove samples. BrC imaginary refractive indices ( k ) were anti-correlated with wavelength dependence ( w ), thus less wavelength dependent BrC had higher light absorptivity. MACbulk, λ correlated with the fraction of OC evolving at higher temperature steps in thermo-optical analysis, consistent with a link between BrC absorptivity and OC volatility, and suggesting that BrC absorption may be parameterized using existing OC data. Modeling analyses showed that BrC makes a strong contribution to overall absorption (average of 48% to 80% at 365 nm), and a strong negative correlation between EC/OA and the relative contribution of BrC to total aerosol (BrC + BC) light absorption; the latter trend is dominated by the quantity versus optical properties of BrC. The estimated direct radiative effect of BrC is approximately equal to that of BC for biofuel combustion emissions in India, highlighting the importance of BrC in the climate energy budget. Copyright © 2022 American Association for Aerosol Research